Centros de Tradições Gaúchas no Oeste do Paraná: a (re)construção da memória coletiva e a fixação de representações. - Szekut, Andressa (2014)
This essay examines the valorization of the gaucho being and the foundation and establishment of Centros de Tradições Gauchas CTGs (Gaucho Traditions Centers) in western Paraná. It seeks to understand the (re)construction of the gaucho being memory in western Paraná after the directed migration, through analyzing the creation of territories, CTGs. It specifically addresses the process of directed migration and colonization in Western Paraná; it studies the (re)construction of the gaucho being‟s collective memory through the CTGs; It analyzes the representations practiced by CTGs in western Paraná, through the identification of symbols and references to the group‟s collective memory; and analyzes the representations of the actions developed by the group for the maintenance and dissemination of their traditions. The research is linked to the perspective of Carlo Ginzburg‟s evidentiary paradigm, following the successive steps: a literature review, based on books and institutional documents that deal with the formation the West Paraná space; analysis of institutional documents, websites and articles directed to traditionalism, about the formation of the Gaucho Traditionalist Movement in Brazil, then historicizing the organization, regulation and influence in the formation of CTGs in western Parana, and finally, analyzing the conjectures supplied by oral sources, field observations and administrative documents, in which the CTGs are founded and established in the region. These steps have. These steps allowed to explore the peculiarities of the construction of the Centers, observe the material and symbolic representations related to the (re)construction of memory, and analyze the guidelines that organize them. In turn, these sources and data were obtained by comprehending the usage of memory as an originator of identity. That allowed us to understand that every action is a maker of space and representations are ways to define references to whatever is intended to be associated to the group, involving material and symbolic proportions. At the same time that allowed understanding that memories and representations created from these centers are forming bonds between their members, both spatial and temporal. Results are measured from these considerations indicating that the CTGs analyzed were founded within the particularities of the colonization of this region; the centers were built targeting the preservation of ties with the identity of the idealized gaucho being and form themselves as territories, organized in regulating activities of sociability; participation in these centers is regulated and the practices (dance, music, gastronomy etc) that are taught through their departments and ritualized through the events, fulfill the task of rememoration and synchronicity; and finally, realize the effort from these centers to consolidate the imaginary and the social representations of the gaucho being , by the affirming of their collective memory in the region.